PENGARUH KUALITAS JASA KURIR TERHADAP MINAT BELI KONSUMEN E-COMMERCE - Dani Leonidas Sumarna; Aditia Sovia Pramudita (Jurnal Ekonomi dan Industri, 2020)
This research was made to determine the relationship between the quality of courier services and buying interest in online transactions. Multivariate statistics are used to answer this problem. The results of this study prove that Logistic Service Quality has a positive influence on buying interest. This shows that the services provided by logistics services have an impact on people's buying interest to shop online.